Late diagnosis of hemangioma. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2012)
A 7 1/2-month-old child was first observed due to the presence of a swelling, which deformed the right upper hemilip. On physical examination (Fig. 2) the swelling hadnot well defined borders, was soft-elastic and compressible, skin-colored but warmer than the surrounding skin. There were no visible telangiectatic vessels on the involved skin. An ultrasonography put in evidence a 22 x 8 mm plaque with prominent vascularity. His parents said that the swelling was present since birth (and provided photographic evidence -Fig. 1-) and had not substantially changed until then. We suspected a venous malformation and decided to clinically monitor the swelling. On the control examination after one year the swelling seemed to be slightly reduced (Fig. 3), but on the next control after another year (Fig. 4) had virtually disappeared, leading to the final diagnosis of hemangioma.